1977
DOI: 10.1080/00365517709091498
|View full text |Cite
|
Sign up to set email alerts
|

Principles of albumin and IgG analyses in neurological disorders. III. Evaluation of IgG synthesis within the central nervous system in multiple sclerosis

Abstract: Fifty-nine multiple sclerosis patients were investigated with regard to blood-brain barrier function by determining the CSF-protein and the CSF/S albumin ratio. Abnormal values were found in 19% and 32% respectively. The occurrence of CSF-IgG elevation due to synthesis within the CNS was analysed by determining the CSF IgG/protein and CSF IgG/albumin ratios and the IgG-index = (CSF/S IgG ratio)/(CSF/S albumin ratio). Increased values were found in 75%, 80% and 86%, respectively. Oligoclonal IgG was found in CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
2
11

Year Published

1979
1979
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(136 citation statements)
references
References 10 publications
4
119
2
11
Order By: Relevance
“…Since anti-GAD antibodies are unable to cross the blood-brain barrier (18), the intrathecal-produced anti-GAD antibodies not from systemic circulation, are essential for the impairment of CNS. In the present case, anti-GAD-specific IgG index (1.62), an assessment index for intrathecal production of anti-GAD antibody (8), was greater than 1.0, thus lending a strong support for its intrathecal production (8,19). In addition, it has been shown that the characteristics of anti-GAD antibodies are different between type 1 diabetes and SPS: anti-GAD65 antibodies in type 1 diabetes may recognize conformational epitopes in the middle and C-terminus of the protein, whereas in SPS they recognize both the linear and conformational epitopes at Nterminus and C-terminus of GAD65 molecules (9,18,20, and 21).…”
Section: Discussionmentioning
confidence: 82%
“…Since anti-GAD antibodies are unable to cross the blood-brain barrier (18), the intrathecal-produced anti-GAD antibodies not from systemic circulation, are essential for the impairment of CNS. In the present case, anti-GAD-specific IgG index (1.62), an assessment index for intrathecal production of anti-GAD antibody (8), was greater than 1.0, thus lending a strong support for its intrathecal production (8,19). In addition, it has been shown that the characteristics of anti-GAD antibodies are different between type 1 diabetes and SPS: anti-GAD65 antibodies in type 1 diabetes may recognize conformational epitopes in the middle and C-terminus of the protein, whereas in SPS they recognize both the linear and conformational epitopes at Nterminus and C-terminus of GAD65 molecules (9,18,20, and 21).…”
Section: Discussionmentioning
confidence: 82%
“…CSF index for LGI1‐IgG and subclasses as compared to serum was calculated according to the Link formula,12 modified for specific antibodies13, 14:LGI1 IgG titer in CSF/ LGI1 lgG titer in serumCSF Albumin (ng/mL)/ serum Albumin (ng/mL) …”
Section: Methodsmentioning
confidence: 99%
“…To characterize local immunoproduction we used Link & Tibbling IgG indices 21 , Tourtellote's daily IgG synthesis 22 , Thompson's nomogram (IgG quotient versus albumin quocient) 23,24 and protein isoelectrofocusing 26 . Anti-Taenia specific antibody indices were calculated by the method established by Reiber and Felgenhauer 7 , using an ELISA assay.…”
Section: Methodsmentioning
confidence: 99%